2020
DOI: 10.2147/ibpc.s232038
|View full text |Cite
|
Sign up to set email alerts
|

<p>Management of Pulmonary Arterial Hypertension in Patients with Systemic Sclerosis</p>

Abstract: Systemic sclerosis (SSc) is a rare and complex immune-mediated connective tissue disease characterized by multi-organ fibrosis and dysfunction. Systemic sclerosisassociated pulmonary arterial hypertension (SSc-PAH) is a leading cause of death in this population. Pulmonary arterial hypertension (PAH) can coexist with other forms of pulmonary hypertension in SSc, including pulmonary hypertension related to left heart disease, interstitial lung disease, chronic thromboembolism and pulmonary venous occlusive disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 108 publications
0
20
0
2
Order By: Relevance
“…Data suggest that SSc-PAH patients who are diagnosed and treated early as a result of screening have improved survival as compared to patients diagnosed following clinical suspicion [47,48]. The following annual strategies have demonstrated similar sensitivity, specificity, positive and negative predictive values [49]. The DETECT algorithm combines two steps.…”
Section: Screening For Ssc-pahmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggest that SSc-PAH patients who are diagnosed and treated early as a result of screening have improved survival as compared to patients diagnosed following clinical suspicion [47,48]. The following annual strategies have demonstrated similar sensitivity, specificity, positive and negative predictive values [49]. The DETECT algorithm combines two steps.…”
Section: Screening For Ssc-pahmentioning
confidence: 99%
“…A decrease in DLCO <60% or >20% in one year in the absence of significant lung volume abnormalities, or an FVC/DLCO percent >1.6 suggests PH [12]. York et al, reported that a DLCO/alveolar volume (Va) of <70% predicted suggested an 18-fold higher risk for developing SSc-PAH within 2.5 years compared with a DLCO/Va >70% [16,49,63].…”
Section: Pulmonary Function Testmentioning
confidence: 99%
“…The endothelin pathway can be blocked by endothelin receptor antagonists. Ambrisentan, bosentan and macitentan are the three endothelin receptor antagonists (ERA) approved for the treatment of SSc–PAH [ 55 ]. Ambrisentan, the only endothelin-1 selective antagonist, was able to improve 6MWD in connective tissue disease (CTD)-associated PAH patients, even though survival was higher in idiopathic PAH patients, in the Ambrisentan in Pulmonary Arterial Hypertension, Randomized, Double-Blind, Placebo-Controlled, Multicenter, Efficacy Study (ARIES) 1 and 2 trials [ 56 , 57 ].…”
Section: Molecular Pathways Targeted By Pah-specific Therapiesmentioning
confidence: 99%
“…PAH is a leading cause of mortality in SSc, with a death rate of around 50% at 3 years (4,5). In the last decades, we experienced important advances in the treatment of SSc associated PAH (SSc-PAH); however, despite the availability of effective treatments, mortality remains high and survival curves are worse than in idiopathic PAH (6).…”
Section: Introductionmentioning
confidence: 99%